PERAN LEMBAGA KEMASYARAKATAN DI DESA DAlAM PEMBERDAYAAN MASYARAKAT (Studi di Desa Cilayung Kecamatan Jatinangor Kabupaten Sumedang Provinsi Jawa Barat) - Vernal Michael Fina (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2018)
Improve their living and prosper society is one of the tasks of government. Efforts community can prosper through community empowerment with the ultimate goal of creating an independent community. In carrying out community development need the involvement of other parties one of which is the village community institutions. The method used in this research is descriptive qualitative inductive approach. Data collection techniques are observation, interviews and documentation. Analysis of the data used in this research is descriptive qualitative data analysis methods. Based on the findings, the authors conclude that Normatively supposed relationship with the Community Institutions Cilayung village government is to be a partnership as set out in legislation. But what happened in the field from local government is less active in the formation of social institutions so that the function of civil society as partners in empowering the village government does not run properly. As for the relationship between the Community Institutions in Rural Cilayung by decree No. 14 of 2007 is a partnership, consultation, and coordination. But the fact that of the seven social institutions studied, among others, RT, RW, Youth, PKK, KPM, LPMD, and Gopoktan, three community organizations of which only established but not running due to misunderstanding of the function of civil society itself. Then the village government strategies and institutions Cilayung kemsyarakatan Cilayung village is a need for the role of companion and extension remain in the village to make an association of villages Cilayung have steering activities within each work program. The village government Cilayung also need training and socialization of how to create regulations and technical skill training for the implementation of the village administration in the village Cilayung. Keywords: role, community, institutions, empowerment